Comparison of Time to Fracture Union and Functional Outcome by Minimally Invasive Plate Osteosynthesis vs Shortened Intramedullary Nailing in Extra-Articular Distal Tibia Fractures - Farooq, Muhammad Saad; Haider, Muhammad Imran; Yousif, Muhammad; Razzaq, Muhammad Noman; Usman, Ahmad; Zia, Muhammad Haseeb (Biological and Clinical Sciences Research Journal, 2025)
Extra-articular distal tibial fractures pose significant management challenges due to the bone's subcutaneous nature and limited soft tissue envelope, increasing the risk of complications. Minimally invasive plate osteosynthesis (MIPO) and shortened intramedullary nailing (IMN) are two commonly employed fixation methods; however, their comparative effectiveness in fracture healing and functional recovery remains uncertain. Objective: To compare the time to radiographic union and functional outcomes between shortened intramedullary nailing (IMN) and minimally invasive plate osteosynthesis (MIPO) in treating extra-articular distal tibial fractures. Methods: A single-center, prospective, randomized controlled trial was conducted from January to December 2024. Sixty skeletally mature patients (aged 20–60 years) with AO classification 43A1–A3 extra-articular distal tibia fractures were randomly assigned to receive either shortened IMN (n=30) or MIPO (n=30). Radiographic healing was assessed using the Radiographic Union Score for Tibial fractures (RUST) at 2 weeks and 3, 4, 5, and 6 months postoperatively. Functional outcome was evaluated using the Olerud-Molander Ankle Score (OMAS) at the final follow-up. Time to union and OMAS grades were compared using chi-square tests, with significance set at p<0.05. Results: A significantly higher proportion of patients in the IMN group achieved union within 12 weeks (66.7%) compared to the MIPO group (26.7%) (p=0.017). Conversely, delayed union beyond 20 weeks was more prevalent in the MIPO group (50.0% vs. 20.0%). Excellent OMAS outcomes were reported in 70.0% of IMN patients versus 20.0% in the MIPO group (p=0.001). The incidence of angular deformity was comparable between groups (IMN: 23.3%, MIPO: 16.7%; p>0.05). Conclusion: Shortened intramedullary nailing leads to earlier radiographic union and superior functional recovery compared to minimally invasive plate osteosynthesis for extra-articular fractures.